2018
DOI: 10.32493/inovasi.v5i2.y2018.p42-61
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH BUDAYA ORGANISASI, GAYA KEPEMIMPINAN DAN PENGAMBILAN KEPUTUSAN TERHADAP KOMITMEN ORGANISASI Studi Kausal pada PT SUCOFINDO (Persero)

Abstract: ABSTRAKPENGARUH BUDAYA ORGANISASI, GAYA KEPEMIMPINAN DAN PENGAMBILAN KEPUTUSAN TERHADAP KOMITMEN ORGANISASI, STUDI KAUSAL PADA PT. SUCOFINDO (Persero). Penelitian ini bertujuan untuk mengetahui pengaruh budaya organisasi, gaya kepemimpinan, dan pengambilan keputusan terhadap komitmen organisasi pada PT. Sucofindo (Persero). Survei dilakukan dengan sampel yang dipilih secara acak dari 100 karyawan. Dengan semua variabel dimasukkan ke dalam matriks korelasi, data kemudian dianalisis dengan teknik jalur. Hasilnya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…According to (Drajat & Maulyan 2020), organizational culture is part of human resource management, seen from behavioral aspects. So that organizational culture is a management behavior adopted by the company to solve problems of internal integration and external adaptation for generations based on corporate philosophy.…”
Section: The Influence Of Organizational Culture On Employee Engagementmentioning
confidence: 99%
“…According to (Drajat & Maulyan 2020), organizational culture is part of human resource management, seen from behavioral aspects. So that organizational culture is a management behavior adopted by the company to solve problems of internal integration and external adaptation for generations based on corporate philosophy.…”
Section: The Influence Of Organizational Culture On Employee Engagementmentioning
confidence: 99%
“…Menurut hasil penelitian Sudaryana menyatakan bahwa faktor lingkungan berpengaruh positif dan signifikan terhadap pengambilan keputusan karir. Hal ini dikarenakan lingkungan dapat mempengaruhi persepsi, nilai-nilai, dan preferensi individu dalam memilih karir (Sudaryana 2021). Misalnya keluarga dapat memberikan pengaruh terhadap pilihan karir individu melalui pengalaman mereka sendiri, harapan yang diharapkan, dan dukungan yang diberikan.…”
Section: Jenis Kelamin Respondenunclassified
“…Similarly, research conducted by Wahyuni (2016) which found that leadership style and organizational culture have an influence on employee performance. In his research, Sudaryana (2015) found that organizational culture has a direct effect on the decision making and commitment of the organization. In addition, leadership also has a direct effect with decision making and organizational commitment and decision making has a direct effect on organizational commitment.…”
Section: Introductionmentioning
confidence: 99%